Hs-CRP and all-cause, cardiovascular, and cancer mortality risk: A meta-analysis. (April 2017) - Li, Yunwei; Zhong, Xiaoming; Cheng, Guanchang; Zhao, Cuihua; Zhang, Lei; Hong, Yan; Wan, Qilin; He, Ruili; Wang, Zhizhong
Abstract: Background and aims: Inconsistent findings have been reported on the association between high-sensitivity C-reactive protein (hs-CRP) and mortality risk. The objective of this meta-analysis was to investigate the association of elevated baseline hs-CRP levels with all-cause, cardiovascular, and cancer mortality risk in the general population. Methods: PubMed and Embase were systematically searched for studies published from inception to October 2016. Prospective observational studies were eligible if they reported the effects of elevated baseline hs-CRP levels on cancer-related, cardiovascular or all-cause mortality in the general population. The pooled adjusted risk ratio (RR) with 95% confidence interval (CI) comparing the highest to the lowest category of hs-CRP levels was used as association measures. Results: A total of 83, 995 participants from 14 studies were identified. When comparing the highest to the lowest category of hs-CRP levels, the pooled RR was 1.25 (95% CI 1.13–1.38) for cancer-related mortality, 2.03 (95% CI 1.65–2.50) for cardiovascular mortality, and 1.75 (1.55–1.98) for all-cause mortality, respectively. Subgroup analysis showed that the effect of elevated hs-CRP levels on cancer-related mortality was observed in men (RR 1.26; 95% CI 1.11–1.43) but not in women (RR 1.03; 95% CI 0.83–1.27). Conclusions: Elevated hs-CRP levels can independently predict risk of all-cause, cardiovascular mortality in the general population. However, the gender differences in the predictive role of hs-CRP on cancer mortality should to be further investigated. Highlights: The predictive value of hs-CRP levels on cancer and all-cause mortality risk is conflicting. Subjects with the highest hs-CRP levels increased by 75% the risk of all-cause mortality. Subjects with the highest hs-CRP levels increased by 2.03-fold the risk of cardiovascular mortality. Hs-CRP can stratify cardiovascular and all-cause mortality risk in the general population. Gender-specific predictive value of hs-CRP on cancer mortality needs to be further investigated.